“Onde está o meu filho?”: a denúncia do desaparecimento de pessoas - França, Paula Marcela Ferreira (2018)
Within the social space, events socially identified as disappearances often stimulates reflection concerning justice, dignity, and well-being, as well as demands for recognition. Such demands are generally aimed solely at police institutions, but in some cases assume the form of protests not always mediated by collective movements. Leading characters in the social objectivisation of this form of drama tend to be victims’ relatives, particularly their mothers. In addition, reports often fail to be pursued by police investigative services or justice departments. Nevertheless, the issue of disappearances in the public space takes the form of a political grammar, marked by a display of suffering that is undeniable and psychologically devastating. The present study is grounded on the efforts and protests of mothers and relatives of missing people in having their reports taken up by public security institutions, whether they seek recognition of their cases through police procedures, the broader justice system or media coverage. I have mapped the moral and political grammars in reports filed by missing people’s mothers and relatives who participated in this study, as well as assessed in public documents the way such protests are appropriated by journalists, intellectuals, public prosecutors, political representatives, mothers supporting non-governmental organizations, and other social agents who act as social critics, i.e. those who establish complaint channels and set the bases for structuring the issue of disappearances in the public forum. The analysis shows how the intervention of social critics in such a dynamic turns one’s attention from the compassion generated by the suffering of mothers and relatives to certain systems and structures; these are regarded as either directly responsible for disappearances – in the cases of state-led violence – or indirectly responsible by failing to produce prevention measures or to locate and punish offenders.